2010
DOI: 10.1002/nme.3024
|View full text |Cite
|
Sign up to set email alerts
|

Hanging nodes and XFEM

Abstract: SUMMARYThis paper investigates two approaches for the handling of hanging nodes in the framework of extended finite element methods (XFEM). Allowing for hanging nodes, locally refined meshes may be easily generated to improve the resolution of general, i.e. model-independent, steep gradients in the problem under consideration. Hence, a combination of these meshes with XFEM facilitates an appropriate modeling of jumps and kinks within elements that interact with steep gradients. Examples for such an interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 52 publications
1
50
0
1
Order By: Relevance
“…Moreover, adaptive hrefinement can be easily implemented in a meshfree context [185][186][187]. Though all methods discussed so far are capable of capturing discrete cracks, a certain refinement around the crack front is still needed for accuracy and efficiency reasons [188]. The meshfree approximation is similar to the FEM formulation:…”
Section: Meshfree Methodsmentioning
confidence: 99%
“…Moreover, adaptive hrefinement can be easily implemented in a meshfree context [185][186][187]. Though all methods discussed so far are capable of capturing discrete cracks, a certain refinement around the crack front is still needed for accuracy and efficiency reasons [188]. The meshfree approximation is similar to the FEM formulation:…”
Section: Meshfree Methodsmentioning
confidence: 99%
“…An alternative idea suggested by [33,34] is to enhance the coarse elements with suitable shape modes, which recover the C 0 continuity between interconnected elements. Although this idea is very appealing and leads to optimal convergence, it has the disadvantage that an extension to high-order shape functions is not straightforward.…”
Section: Classical Refinement Schemesmentioning
confidence: 99%
“…Fries et al [20] reported two approaches to adapt quadtree meshes into the extended finite element method. The first approach uses the transition elements developed by Gupta [14].…”
Section: Introductionmentioning
confidence: 99%